Fortalecimiento de las competencias comunicativas, un reto de la licenciatura en educación básica primaria - Balaguera Balaguera, Constanza (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This article presents a reflection on the challenges and needs of the students of the Primary Bassic Education Degree, in terms of performance as competent speakers, a task adressed in the first intance through the subject of Communicative Competences and then in the other subjects in the área of Spanish Language, taking into account that language is the human capacity that allows to construct, express, disseminate and universalize thought. In addition, being communication a compe- tence made up of skills such as speaking, listening, reading and writing, it is urgent to take actions that help students to improve and strengthen them, especially when all these are necessary for an adequate performance in the course of his university career. Based on the statements made by them through the characterization survey applied to the students of the first semester of the program, regarding the need to strengthen some aspects related to language skills, especially in reading and writing, it reflects the urgency that they feel about improving their communication skills not only in the academic sphere but also in the context in which they perform. Finally, a reflection is made on the challenge of working to strengthen communicative skills in the students of the program, undertaken from all subjects with the help of both teachers and students involved in the teaching-learning process.